2020
DOI: 10.1111/jocs.14991
|View full text |Cite
|
Sign up to set email alerts
|

Why should cardiac surgeons occlude the left atrial appendage percutaneously?

Abstract: Objectives: Percutaneous left atrial appendage (LAA) occlusion (LAAO) is a procedure dominated by cardiologists. The aim of our study was to present the results of percutaneous LAAO performed solely by cardiac surgeons. Methods: Two hundred twenty-three consecutive patients with nonvalvular atrial fibrillation underwent percutaneous LAAO in two cardiac surgery sites. In the first center, all 84 LAAO procedures were performed with the endocardial LAA occluders: 60 cases with the Amulet and 24 cases with the LAm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…All interventions were performed by surgeons, who had undergone pretraining in a simulation model. Soon, thereafter, they were able to achieve outcomes that were comparable with those obtained by experienced interventional cardiologists 1 …”
mentioning
confidence: 63%
See 2 more Smart Citations
“…All interventions were performed by surgeons, who had undergone pretraining in a simulation model. Soon, thereafter, they were able to achieve outcomes that were comparable with those obtained by experienced interventional cardiologists 1 …”
mentioning
confidence: 63%
“…In this issue of the Journal, Litwinowicz et al 1 describe their trailblazing experience in 223 consecutive patients in whom they performed left atrial appendage occlusion (LAAO) via the percutaneous route. All interventions were performed by surgeons, who had undergone pretraining in a simulation model.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Three hundred and nine articles were obtained by online and manual searches. After removing duplicates, screening titles and abstracts, four independent trials [25][26][27][28] contained data for the LAmbre occluder versus other LAAC devices were selected that included 607 patients (142 randomized to the LAmbre occluder and 465 to other LAAC devices). (Figure 1) (as seen in the flow chart).…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
“…23,24 Some studies compared the clinical outcomes of the LAmbre occluder to those of other LAAC devices, which with contradictory results. The LAmbre occluder had a higher rate of device-related thrombus(DRT) than other LAAC devices, according to Schnupp et al 25 and Chen et al 26 , whereas Litwinowicz et al 27 found the opposite. The goal of this study was to compare the safety and efficacy of the LAmbre occluder to that of other LAAC devices.…”
Section: Introductionmentioning
confidence: 99%